2017
DOI: 10.1002/14651858.cd012509.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events associated with medium- and long-term use of opioids for chronic non-cancer pain: an overview of Cochrane Reviews

Abstract: A number of adverse events, including serious adverse events, are associated with the medium- and long-term use of opioids for CNCP. The absolute event rate for any adverse event with opioids in trials using a placebo as comparison was 78%, with an absolute event rate of 7.5% for any serious adverse event. Based on the adverse events identified, clinically relevant benefit would need to be clearly demonstrated before long-term use could be considered in people with CNCP in clinical practice. A number of advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
211
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(234 citation statements)
references
References 81 publications
3
211
3
6
Order By: Relevance
“…We identified 14 systematic reviews that directly addressed this element, and also synthesized relevant findings from three systematic reviews developed to inform the recent guidelines for opioids for chronic noncancer pain. (99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112) With respect to reducing the emergence of chronic pain, we found no systematic reviews about how to prevent the transition to chronic pain, but we found seven systematic reviews that related to the education of the public and health professionals as part of a broadly based prevention effort. Three recent reviews (two high-quality and one medium-quality) and four older medium-quality reviews evaluated the effectiveness of mass-media campaigns targeted at both groups.…”
Section: Element 2 -Reduce the Emergence Of Chronic Pain And Its Sequmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 14 systematic reviews that directly addressed this element, and also synthesized relevant findings from three systematic reviews developed to inform the recent guidelines for opioids for chronic noncancer pain. (99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112) With respect to reducing the emergence of chronic pain, we found no systematic reviews about how to prevent the transition to chronic pain, but we found seven systematic reviews that related to the education of the public and health professionals as part of a broadly based prevention effort. Three recent reviews (two high-quality and one medium-quality) and four older medium-quality reviews evaluated the effectiveness of mass-media campaigns targeted at both groups.…”
Section: Element 2 -Reduce the Emergence Of Chronic Pain And Its Sequmentioning
confidence: 99%
“…Given the low quality of evidence overall and the heterogeneity across the different interventions, results should be interpreted with caution. Overview of adverse events associated with medium-and long-term use of opioids for chronic noncancer pain (112) This review included 16 Cochrane Reviews detailing the adverse events associated with medium-and long-term use of opioids for chronic non-cancer pain (CNCP).…”
Section: Studies Comparing Back School Treatment With Other Active Inmentioning
confidence: 99%
“…Además, los opioides favorecen neuroadaptaciones que disminuyen su capacidad para proporcionar analgesia a medio y largo plazo, produciendo efectos opuestos, es decir, el aumento del dolor existente (hiperalgesia inducida por opioides) y la facilitación del desarrollo del dolor crónico (Lavand'homme y Steyaert, 2017). Otros estudios enumeran complicaciones del uso de opiáceos para el dolor crónico no oncológico, que deben ser tenidas en cuenta (Els et al, 2017). Por estas razones y por la limitada utilidad de los opioides en el tratamiento del dolor crónico no se recomienda en la actualidad su uso extrahospitalario, mucho menos en dolores moderados o leves (Ashburn y Fleisher, 2018).…”
Section: Introductionunclassified
“…This is mainly because although the effectiveness of opioids is well recognised for the relief of moderate to severe acute pain and cancer‐related pain, the chronic use of opioids for the treatment of chronic non‐cancer pain (CNCP) is not recommended because of the unproven benefits of long‐term opioid use in CNCP . Opioids have also been associated with adverse effects, the development of tolerance to the analgesic effect, fatal drug overdose, addiction and drug diversion in patients with CNCP . The guidelines for opioid prescribing for CNCP recommend treatment with opioids in carefully monitored and selected patients, particularly those without a history of substance abuse and psychiatric comorbidities …”
Section: Introductionmentioning
confidence: 99%